Three-Dimensional Joint Inversion of Borehole and Surface Magnetic Data of the Cangyi Iron Mine, Shandong Province (East China) - Zhang, Jiantai; Cao, Hecai; Zhu, Chenghe; Jian, Xiange; Sun, Yongsheng; Li, Yu; Guo, Changsheng; Yuan, Liwei; Yu, Lei; Du, Xianfu (IEEE geoscience and remote sensing letters, 2025)
The Cangyi iron ore belt is a geologically significant sedimentary-metamorphic iron ore belt in China. The transition from open-pit mining to underground mining in the belt is primarily driven by the depletion of surface resources, necessitating the exploration of deep-seated deposits. However, the distribution of these deposits in the Cangyi iron ore belt is intricately controlled by basement fold structures and exhibits late-stage modifications, posing challenges for accurate evaluations of the ore deposits. This study uses a surface magnetic survey to map the planar distribution of the ore bodies. Via 3-D joint inversion of borehole and surface magnetic data, the planar and deep-seated distribution of magnetic iron ore in the belt is obtained. The joint inversion of surface and borehole magnetic data enhances the vertical and horizontal resolutions of deep-seated magnetic sources. This approach is a crucial geophysical method for exploring and characterizing deep mineral resources. Reliance on surface structural traces alone is insufficient for accurate reconstructions of deep structures. Using magnetite inferred from the joint inversion as a marker layer and analyzing the structural trace of the deposit is essential to evaluating the deposit. Previous speculation regarding the presence of a deep-seated ore body at a depth of 1400 m in the exploration area is dispelled by joint inversion of borehole-surface magnetic data, which reveals the absence of highly magnetized magnetic bodies at a depth of 1300 m. This finding provides a clear direction for further deep exploration.